Mucosal Vaccination for Influenza Protection Enhanced by Catalytic Immune‐Adjuvant - Tao Qin (Advanced Science, 2020)
Abstract Influenza poses a severe threat to global health. Despite the whole inactivated virus (WIV)‐based nasal vaccine being a promising strategy for influenza protection, the mucosal barrier is still a bottleneck of the nasal vaccine. Here, a catalytic mucosal adjuvant strategy for an influenza WIV nasal vaccine based on chitosan (CS) functionalized iron oxide nanozyme (IONzyme) is developed. The results reveal that CS‐IONzyme increases antigen adhesion to nasal mucosa by 30‐fold compared to H1N1 WIV alone. Next, CS‐IONzyme facilitates H1N1 WIV to enhance CCL20‐driven submucosal dendritic cell (DC) recruitment and transepithelial dendrite(TED) formation for viral uptake via the toll‐like receptor(TLR) 2/4‐dependent pathway. Moreover, IONzyme with enhanced peroxidase (POD)‐like activity by CS modification catalyzes a reactive oxygen species (ROS)‐dependent DC maturation, which further enhances the migration of H1N1 WIV‐loaded DCs into the draining lymph nodes for antigen presentation. Finally, CS‐IONzyme‐based nasal vaccine triggers an 8.9‐fold increase of IgA‐mucosal adaptive immunity in mice, which provides a 100% protection against influenza, while only a 30% protection by H1N1 WIV alone. This work provides an antiviral alternative for designing nasal vaccines based on IONzyme to combat influenza infection.